Accurate diagnosis of carriers of deletions and duplications in Duchenne/Becker muscular dystrophy by fluorescent dosage analysis. Issue 7 (July 1996) - Yau, S C; Bobrow, M; Mathew, C G; Abbs, S J
Abstract : We have developed a semiautomated approach to amplify 25 exons of the dystrophin gene using two fluorescent multiplex PCR assays which detect over 98% of reported deletions and 90% of duplications causing Duchenne/Becker muscular dystrophy. The 5' multiplex detects 11 exons from the proximal deletion hotspot of the gene while the 3' multiplex detects 14 exons from the central deletion hotspot. The PCR products are accurately sized and quantified by a fluorescent DNA sequencer after only 18 cycles of amplification. The amount of product amplified from each exon in a multiplex is divided by that from each of the other exons, and this ratio is compared with those from control samples to obtain a series of dosage quotients (DQ), from which the copy number of each exon is determined. No overlap was observed between the DQ values obtained from single and double copy loci. The assays can be used to screen both affected males and at risk female relatives for a mutation. The method has been evaluated as a female carrier test by conducting a blind trial on 150 coded samples. Sixty-three deletion carriers, two duplication carriers, and 84 normal female controls were all correctly identified, showing that carrier diagnosis is possible even in families where the nature of the mutation is unknown. Additionally the analysis showed a non-pathogenic duplication involving the muscle specific promoter and exon 1. Together these two multiplex assays detect over 70% of all mutations in the dystrophin gene, greatly simplifying and partly automating molecular diagnosis in Duchenne and Becker muscular dystrophy.